2011
DOI: 10.5539/elt.v4n4p36
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of EFL Teachers’ and Intermediate High School Students’ Perceptions of Written Corrective Feedback on Grammatical Errors

Abstract: This study was an attempt to compare EFL teachers' and intermediate high school students' perceptions of written corrective feedback on grammatical errors and also to specify their reasons for choosing comprehensive or selective feedback and some feedback strategies over some others. To collect the required data, the student version of questionnaire developed for the purposes of this study was distributed to 100 intermediate high school students who were selected based on their scores on a proficiency test. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
7

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
3
17
0
7
Order By: Relevance
“…(Evans, 2012) also found that direct unfocused teacher direct feedback can be effective in improving accuracy. Moreover, providing different systems of error and feedback categorization to help research the properties of language teachers' feedback outcome in student papers (Jodaie, Farrokhi, & Zoghi, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(Evans, 2012) also found that direct unfocused teacher direct feedback can be effective in improving accuracy. Moreover, providing different systems of error and feedback categorization to help research the properties of language teachers' feedback outcome in student papers (Jodaie, Farrokhi, & Zoghi, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…There were several empirical studies which focused on students' and teachers' perception of written corrective feedback. These studies also examined the ways to make use of students' and teachers' perceptions to enhance the effectiveness of written corrective feedback (Amrhein & Nassaji, 2010;Dowden et al, 2013;Jodaie, Farrokhi, & Zoghi, 2011;McCarthy, 2013;Evans, Hartshorn, & Tuioti, 2010;Lee, 2008;Robinson, Pope, & Holyoak, 2013;Weaver, 2006). Dowden et al (2013) suggest that teacher and students have to work closely to solve the misunderstanding or miscommunication in the process of giving feedback.…”
Section: Claim 2: Students' and Teachers' Perceptions Affect The Effementioning
confidence: 99%
“…Se concibe como un proceso en el cual se comunican al estudiante sus aciertos, pero especialmente sus errores, mediante símbolos, marcas, cruces, vistos y puntajes Harris, Irving & Peterson, 2008;Jodaie, Branch, Farrokhi & Zoghi, 2011;. Para los profesores, es una manera rápida y clara de identificar los errores, por ejemplo, con subrayados o círculos.…”
Section: Retroalimentación Entendida Como Correcciónunclassified
“…Por otra parte, en los estudios con profesores que se desempeñan enseñando una segunda lengua (Jodaie, Branch, Farrokhi & Zoghi, 2011;, la retroalimentación como corrección es usada de manera preferencial. Esto se comprende dada la naturaleza de la enseñan-za y la evaluación en una segunda lengua, ya que se compone en gran parte por aspectos formales y de estructura, lo cual sugiere que el contenido que se evalúa confiere algún tipo de especificidad al tipo de retroalimentación que se otorga y, por lo tanto, a las concepciones que la orientan.…”
Section: Consideraciones Finalesunclassified